Experience and Behavior: How Negative Feedback in New Versus Experienced Domains Affects Firm Action and Subsequent Performance - Eggers, J. P.; Suh, Jung-Hyun (Academy of Management Journal, 2019)
How organizations respond to failure (negative feedback) has important implications for subsequent organizational performance. This study focuses on theoretical and empirical distinctions between the different potential organizational reactions to failure (in this case around new product development) and how those feedback-driven choices aggregate to affect firm performance. To understand when and why negative feedback is organizationally beneficial, we focus on how possession of domain-specific experience affects the way in which firms interpret and respond to negative feedback, offering both organization- and mechanism-level theories. In particular, we distinguish between conditions that should lead to different behavioral responses to negative feedback: retreat, local search, or distant search. We find support for our theory using data on all U.S. mutual fund companies from 1962 to 2002, and testing both aggregated and mechanism-level theories. Our results show that negative feedback on new funds launched in new domains is particularly damaging to subsequent organizational performance, as firms retreat from the unknown in favor of already exploited domains. In contrast, negative feedback in experienced domains can produce positive outcomes by encouraging action to search for both local solutions to correct the problem and distant solutions to expand the firm’s opportunities.